Perceptions of medical doctors living in Ethiopia about physician migration: a qualitative study - Ephrem Tadele Sedeta; Temesgen Beyene Abicho; Bilain Yilma Jobre (BMJ Open)
Objectives Migration of physicians is one of the most pressing global health problems of our time with the greatest implications in sub-Saharan African countries. Although other studies have explored and produced important quantitative data about the impact of medical migration in the health sector of Ethiopia, the motive behind Ethiopian physician migration have been explored less thoroughly. This article explores the perceptions of a group of physicians about the complicated and continuously evolving driving forces of physician migration in Ethiopia.Design Qualitative study using in-depth, virtual semistructured interviews.Participants Using purposive sampling, 12 physicians participated.Setting Skype interviews with 12 participants working in Tikur Anbessa Specialised Hospital in Addis Ababa, Ethiopia.Results Four themes emerged reflecting the perceptions of Ethiopian medical doctors on the driving forces of physician migration: (1) Economic push and pull factors; (2) Professional push and pull factors; (3) Social and Political push and pull factors and (4) Medical migration governance.Conclusion The emigration of Ethiopian physicians is made after weighing the push and pull factors. Push factors are more crucial than pull factors, and financial reasons play the leading role. Junior physician unemployment, politicisation of hospital administration, and poor medical migration governance are growing problems. Junior physician unemployment is a recent phenomenon in Ethiopia and with a potential to be a leading push factor if appropriate intervention is not taken. The findings of this study are worrying and urge for comprehensive solutions to be devised by policy-makers to deal with physician migration in Ethiopia.